A CASE STUDY ABOUT THE ECHOES OF APPLICATIONS USED IN ON-LINE MUSICAL EDUCATION, ON CHILDREN AGED 8-15, THROUGH THE PERIOD OF COVID-19 - Göksen TOSUNER (Fırat University, 2020)
This study is done due to understand and describe the effects of on-line music lessons, levels of learning and lecturing sessions during the period of Covid-19's social ısolations. Though it is not a general study of its concept; it's related to a qualitative search on traditional studies. The main subject where this work focuses on, is the question that how does this Covid-19 pandemic effect the students' on-line lessons and levels of learning. In order to find an answer to that question, the students aged 8-15, taking on-line lessons from Kayseri (National Education Ministry) Katre Music School, were included to this study and monitored and watched for their attitudes during the period, within the research notes and students' diaries. In addition to those data sets (notes) taken from the students, some advices, about child development and pedagogy, were also obtained from the consultants and (or) supervisors. When at the part of analyzing of the study, all the obtained datas' analysis were realized by thematic and colored (coloured) codings. To increase the reliability and the validity of the codings that used through the research, 3 colleagues of specialist were also included to the study. To obtain additional knowledge to the study subjoining the open-ended question (quest) types of nitel works, a 10 questioned survey of 5 point Likert scale was used to figure out the efficiency of the education and also the experiences of the 20 students who took piano lessons via the on-line education modeling. Within the conclusions of findings during the research period, it was seen that, to achieve an efficient and uninterrupted process using the on-line education modeling in music lessons, some specific technological devices and high speed internet infrastructures are needed. In this direction, it was concluded as; by taking regular musical education, the multiple earnings positively affected the student's daily life through this isolation time.